2003
DOI: 10.1093/carcin/bgg099
|View full text |Cite
|
Sign up to set email alerts
|

WY-14,643-mediated promotion of hepatocarcinogenesis in connexin32-wild-type and connexin32-null mice

Abstract: Connexin32 (Cx32) is the major gap junction forming protein in liver and lack of functional Cx32 enhances hepatocarcinogenesis. Many tumour-promoting agents block gap junctional intercellular communication, which may favour clonal expansion of neoplastic cells. We recently demonstrated that liver tumourigenesis is accelerated in Cx32-wild-type but not in Cx32-null mice by the model tumour promoter phenobarbital (PB). In the present study, male Cx32-wild-type and Cx32-null mice were treated with a single inject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
56
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 25 publications
2
56
0
1
Order By: Relevance
“…It is noteworthy, however, that the incidence of liver tumors is much higher in male as compared to female mice demonstrating the involvement of sex hormones in liver tumor development. 39 Even though the long-term effects of Cx32-deficiency on chemically induced hepatocarcinogenesis in mouse liver are rather dramatic, [5][6][7] we did not observe a concomitant strong change in the expression of a particular gene that could explain the strainspecific differential behavior. A comparable microarray analysis carried out with a conditional Cx26-deficient mouse also showed only very few genes that were moderately altered in expression in liver of the gene knockout mice (T.O., unpublished observation).…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…It is noteworthy, however, that the incidence of liver tumors is much higher in male as compared to female mice demonstrating the involvement of sex hormones in liver tumor development. 39 Even though the long-term effects of Cx32-deficiency on chemically induced hepatocarcinogenesis in mouse liver are rather dramatic, [5][6][7] we did not observe a concomitant strong change in the expression of a particular gene that could explain the strainspecific differential behavior. A comparable microarray analysis carried out with a conditional Cx26-deficient mouse also showed only very few genes that were moderately altered in expression in liver of the gene knockout mice (T.O., unpublished observation).…”
Section: Discussionmentioning
confidence: 58%
“…1,2 In accordance with this hypothesis, PB treatment resulted in promotion of hepatocarcinogenesis in Cx32wt mice, whereas no such effect was observed in Cx32ko mice suggesting that functional Cx32 is required for promotional activity of the barbiturate. 7 Because it is well established that PB not only affects (pre)neoplastically transformed cells but also modulates the expression of various genes within normal hepatocytes, we hypothesized that the analysis of PBmediated changes in gene expression in the normal liver tissue from Cx32wt and Cx32ko mice might give us some hint on the mechanism underlying the tumor promotional activity of the barbiturate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The age of mice at DEN injection is highly relevant since, in C3H mice, it has been shown that PB inhibits hepatocarcinogenesis when the initiator DEN is given to 2-week-old mice, whereas it promotes tumorigenesis after DEN injection at 6 weeks of age (Moennikes et al 2000). Comparably, PB inhibits tumor development in DENinduced (2 weeks) mice from strain B6C3F1, a crossbreed of C3H and C57BL/6 (Diwan et al 1984;Klaunig et al 1987Klaunig et al , 1988Lee et al 1998).…”
mentioning
confidence: 99%
“…CAR may regulate those factors through gene expressions, as well as direct protein-protein interactions. No consensus on what these factors may be has arisen yet, although c-Jun, FoxM1B, Connexin32, and Mdm2 have been suggested as candidates (Eferl et al, 2003;Kalinichenko et al, 2004;Moennikes et al, 2000, Huang et al, 2005. Although PB has been used to treat epilepsy patients for decades, liver tumors have never been associated with PB treatment, PB does not cause Drug Metabolism Reviews Downloaded from informahealthcare.com by McMaster University on 11/20/14…”
mentioning
confidence: 99%